MCP-1 AND VITAMIN D PROFILES IN ESRD ON HEMODIALYSIS: A CASE-CONTROL STUDY IN AL-BASRAH CITY - Fadhil , Haneen Husham; Salman , Rana Dawood; Hasan , Jubran Khaleel (PT. Antis International Publisher, 2025)
Objective: This study aimed to examine and compare serum levels of vitamin D and monocyte chemoattractant protein-1 (MCP-1) in patients with end-stage renal disease (ESRD) undergoing haemodialysis versus healthy individuals, and to evaluate their diagnostic potential as biomarkers. Method: An observational cross-sectional design was employed involving 30 ESRD patients receiving regular haemodialysis and 34 age- and sex-matched healthy controls. Serum levels of vitamin D, MCP-1, parathyroid hormone (PTH), urea, creatinine, estimated glomerular filtration rate (eGFR), and blood pressure were assessed. Results: ESRD patients showed significantly elevated levels of urea, creatinine, PTH, and MCP-1, and significantly lower eGFR and vitamin D levels compared to controls (p<0.001). ROC analysis revealed high diagnostic accuracy for PTH (AUC=0.946), with moderate-to-good performance for vitamin D (AUC=0.732) and MCP-1 (AUC=0.700). Novelty: This study contributes to the limited regional data by identifying the potential of vitamin D and MCP-1 as accessible clinical biomarkers for nutritional and inflammatory assessment in ESRD patients undergoing haemodialysis, emphasizing their role in early detection strategies and patient monitoring.